The relationship between life satisfaction and risk preferences of couch potatoes, recreational and elite athletes: the impact of mental dispositions and attitudes - Aguiar-Noury, Alice; Frick, Bernd; Risch, Nikolaus (Frontiers in Behavioral Economics, 2024)
IntroductionThis study examines the relationship between physical activity and mental wellbeing among students not playing any sport (“couch potatoes”), recreational athletes and “dual career students”, i.e., students who are at the same time elite athletes. It addresses three closely related, yet different questions: (i) Do couch potatoes, recreational and elite athletes differ in their level of affective well-being or happiness? (ii) Are there any differences in cognitive wellbeing or life satisfaction between these groups? and (iii) Are there any differences in risk preferences and attitudes?MethodsIn our empirical analysis, we use a large cross-section dataset with detailed information on nearly 4,700 students enrolled at 24 different universities and universities of applied sciences all over Germany to identify the relationship between the individuals' personalities and their life satisfaction and risk preferences using standard regression models.ResultsOur findings indicate that, first, elite athletes report higher levels of happiness and life satisfaction than recreational athletes and couch potatoes. Second, both groups of athletes display higher levels of risk tolerance than couch potatoes. Third, and most important, we find significant personality differences between elite athletes and the other two groups of students that drive most, yet not all of our results.DiscussionSince dual career students are often role models for other students, universities should consider investing in their sports facilities and offering sports classes on campus to increase the athletic involvement of the general student body.